Impact of Freezing Time and Balloon Size on the Thermodynamics and Isolation Efficacy During Pulmonary Vein Isolation Using the Second Generation Cryoballoon. (August 2015) - Takami, Mitsuru; Lehmann, H. Immo; Misiri, Juna; Parker, Kay D.; Sarmiento, Ray I.; Johnson, Susan B.; Packer, Douglas L.
<x xml:space="preserve">Abstract</x> Background— The differences in ablation characteristics of freezing time and balloon size using second generation cryoballoon are still unknown. Methods and Results— Twenty-six dogs underwent pulmonary vein (PV) isolation. Balloon and tissue temperatures (left atrial–PV junction, phrenic nerve, and internal esophagus) were monitored. The ablation duration was randomized to either 3 or 4 minutes, which did not show significant differences in temperature profiles, PV isolation success rate, complications, or histological changes. Twenty dogs underwent cryoablation using 28-mm cryoballoon, 6 dogs were done using the 23-mm cryoballoon. Positioning of the 23-mm cryoballoon was more distal in the PV, which resulted in better PV occlusion. Temperature profiles showed lower temperatures in the 23-mm cryoballoon than in the 28-mm cryoballoon (inner balloon, median [range]: −51.5 [−66.0 to −31.0] versus −43.0 [−64.0 to −26.0]°C, P<0.001; balloon surface: −43.0 [−60.0 to −15.8] versus −6.5 [−46.2 to 28.9]°C, P<0.001; left atrial–PV junction: −6.7 [−20.0 to 21.4] versus 15.8 [−14.4 to 35.1]°C, P<0.001), and trended toward a higher PV isolation success rate in the 23-mm cryoballoon. Histologically, deeper extensions of ablative lesions into the PV were seen with 23-mm cryoballoon, and larger ablative lesions were seen in the left atrial antrum using 28-mm cryoballoon. Conclusions— The efficacy of 3-minute ablation was not significantly different from 4-minute ablation in dogs. The 23-mm cryoballoon had a greater cooling effect than the 28-mm cryoballoon for small PVs, but showed narrower ablative lesions in the left atrial antrum.